A Prospective Evaluation of Fatigue in Pediatric Brain Tumor Patients Treated With Radiation Therapy. (November 2022) - Gandy, Kellen; Chambers, Tiffany; Raghubar, Kimberly P.; Fatih Okcu, Mehmet; Chintagumpala, Murali; Taylor, Olga; Mahajan, Anita; Kahalley, Lisa S.; Chan, Wenyaw; Grosshans, David R.; Brown, Austin L.; Douglas Ris, Martin
Background: Fatigue is a well-established consequence of cranial radiotherapy in survivors of pediatric brain tumor, but less is known about acute fatigue during radiotherapy treatment. This study aimed to longitudinally evaluate fatigue in newly diagnosed pediatric patients with brain tumors during treatment.Methods: Primary caregivers of pediatric patients with brain tumors completed the proxy-reported Parent Fatigue Scale assessments prior to radiotherapy and weekly during radiotherapy treatment. The association between clinical factors and fatigue at each assessment was evaluated with multiple linear regressions. A comparison of fatigue between radiation modalities was also analyzed.Results: A total of 33 caregivers completed pre-radiation fatigue assessments, with 29 reporting fatigue during radiotherapy. Patients were aged 3 to 16 years ( M  = 8.32) at diagnosis and diagnosed with medulloblastoma ( n  = 23), primitive neuroectodermal tumor ( n  = 2), ependymoma ( n  = 1), germ cell tumor ( n  = 1), pineoblastoma ( n  = 1), atypical teratoid rhabdoid ( n  = 1), and other unspecific tumors ( n  = 3). Moderate-to-severe fatigue was reported for the majority of patients (31/33; 94%) during treatment. Craniospinal irradiation dose was the only significant predictor of fatigue ( p  < .05), but this association was restricted to the first week of therapy and was attenuated by therapy completion.Discussion: Although fatigue is often considered a long-term consequence of cranial radiotherapy, this pilot study demonstrates that moderate-to-severe fatigue is pervasive prior to radiotherapy and persists throughout treatment in pediatric patients with brain tumors, regardless of radiation modality or clinical factors. Additional research is warranted to establish a link between acute and long-term fatigue and develop interventions to mitigate this adverse outcome.